2016
DOI: 10.1007/978-3-319-40229-1_27
|View full text |Cite
|
Sign up to set email alerts
|

Interval Temporal Logic Model Checking: The Border Between Good and Bad HS Fragments

Abstract: Abstract. The model checking problem has thoroughly been explored in the context of standard point-based temporal logics, such as LTL, CTL, and CTL ⇤ , whereas model checking for interval temporal logics has been brought to the attention only very recently. In this paper, we prove that the model checking problem for the logic of Allen's relations started-by and finished-by is highly intractable, as it can be proved to be EXPSPACE-hard. Such a lower bound immediately propagates to the full Halpern and Shoham's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…We prove that, as expected, HS lin is not comparable with either of the branching versions, HS ct and HS st . The interesting result is that, on the other hand, HS ct is strictly included in HS st : this supports HS st , adopted in [30,31,32,33,7,9], as a reasonable and adequate semantic choice.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…We prove that, as expected, HS lin is not comparable with either of the branching versions, HS ct and HS st . The interesting result is that, on the other hand, HS ct is strictly included in HS st : this supports HS st , adopted in [30,31,32,33,7,9], as a reasonable and adequate semantic choice.…”
Section: Introductionsupporting
confidence: 60%
“…To this end, we restrict our attention to the fragment BE lin . Since modalities 〈B〉 and 〈E〉 only allow one to 'move' from an interval to its subintervals, BE lin actually coincides with BE st , whose MC is known to be hard for EXPSPACE [7]. Thus, in particular, it is possible to encode by means of a BE lin formula ψ cpt the (unique) computation of a deterministic Turing machine using b(n) ∈ O(2 n ) bits that, when executed on input 0 n , for some natural number n ≥ 1, counts in binary from 0 to 2 2 n − 1, by repeatedly summing 1, and finally accepts.…”
Section: Corollary 34 Hs Lin and Ltl Have The Same Expressive Powermentioning
confidence: 99%
“…In that paper, the authors showed that finite Kripke structures can be suitably mapped into interval-based structures, called abstract interval models, over which HS formulas can be interpreted. Then, they proved a small model theorem showing (with a non-elementary procedure) the decidability of MC for full HS, which was later proved to be EXPSPACE-hard by Bozzelli et al in [8]. 1 The MC problem for some large fragments of HS was studied in [8,37,38].…”
Section: Related Workmentioning
confidence: 99%
“…Then, they proved a small model theorem showing (with a non-elementary procedure) the decidability of MC for full HS, which was later proved to be EXPSPACE-hard by Bozzelli et al in [8]. 1 The MC problem for some large fragments of HS was studied in [8,37,38]. In [38], Molinari et al devised an EXPSPACE MC algorithm for the HS fragment AABBE (resp., AAEBE) of Allen's relations meets, met-by, starts, finishes, and started-by (resp., finished-by), which exploits the possibility of finding, for each trace (of unbounded length), an equivalent bounded-length trace representative in such a way that, while checking a property, the algorithm only needs to consider traces whose length does not exceed the given bound.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation